The Role of Social Media in Enhancing Language Learning - Ernestivita, Gesty; Mendes, Clara; Rocha, Thiago (Journal International Inspire Education Technology, 2024)
The rise of social media has significantly impacted various aspects of education, including language learning. Social media platforms offer interactive and engaging environments where learners can practice and develop language skills outside the traditional classroom setting. This study aims to evaluate the role of social media in enhancing language learning, focusing on its effectiveness in improving learners’ communication skills, vocabulary acquisition, and cultural awareness. A mixed-methods research design was employed, combining quantitative surveys and qualitative interviews. Data were collected from 200 language learners who actively use social media for educational purposes. The quantitative analysis focused on measuring improvements in language proficiency, while qualitative interviews provided deeper insights into learner experiences and the specific ways social media platforms support language development. The results indicate that 80% of participants reported improvements in their communication skills, particularly in informal conversation and writing, through social media interactions. Additionally, 70% of learners noted significant vocabulary acquisition due to exposure to native speakers and authentic language content. The study also revealed that social media enhances cultural understanding by exposing learners to diverse language contexts and real-world usage. In conclusion, social media plays a valuable role in enhancing language learning by providing learners with accessible and interactive platforms to practice and improve their skills. However, its effectiveness depends on the learner’s level of engagement and the quality of content consumed. Future research should explore strategies for optimizing social media use in formal language education settings.